DARI REGULASI KE REALISASI: IMPLEMENTASI UNIT LAYANAN DISABILITAS DALAM KETENAGAKERJAAN INKLUSIF DI KABUPATEN BANDUNG BARAT - Zairusi Zairusi (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study analyzes the implementation of the Disability Service Unit (Unit Layanan Disabilitas/ULD) in promoting inclusive employment for persons with disabilities in West Bandung Regency. Although the local government has established a regulatory framework through Regional Regulation Number 8 of 2019 on Manpower Administration and has formally formed the ULD in the employment sector, the actual absorption of workers with disabilities remains limited. Of 573 persons with disabilities of productive age, only 77 are employed in the formal sector, while only 11 of 760 registered companies employ persons with disabilities. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using Van Meter and Van Horn's public policy implementation framework. The findings indicate that the limited effectiveness of the ULD is influenced by institutional resource constraints, weak inter-actor communication, low commitment among business actors, inadequate industry-based vocational training, and persistent social stigma toward persons with disabilities. The study confirms that inclusive employment cannot be achieved merely through regulatory and institutional formation; it requires institutional capacity, multi-stakeholder collaboration, and organizational culture change. This article recommends strengthening the ULD as an integrated center for services, advocacy, training, job placement, and post-placement monitoring for workers with disabilities.